CO2 sensing properties and mechanism of ZnMn2O4 nanotubes under air and inert conditions. Issue 18 (25th April 2022) - Hu, Jiahao; Zhang, Tao; Chen, Ying; Xu, Pengcheng; Zheng, Dan; Li, Xinxin
Abstract : ZnMn2 O4 nanotube based CO2 sensor and sensing mechanism study. Abstract : With the increasing usages of fossil fuels, CO2 is excessively produced and brings serious greenhouse effects. It is important to detect the concentrations of CO2 in many application fields such as environmental monitoring and health care. Herein, ZnMn2 O4 nanotubes have been successfully synthesized and used as a sensing material for CO2 detection. The mean diameter of the ZnMn2 O4 nanotubes is measured as approximately 100 nm and the wall thickness was measured as 41 nm. By loading the ZnMn2 O4 nanotubes onto a lab-made micro-hotplate, a MEMS sensor for CO2 detection was fabricated. The sensing experiments indicate that the ZnMn2 O4 nanotubes exhibit a good sensing response to CO2 gas with concentrations in the range of 2.5–100% under both air and N2 atmospheres. The ZnMn2 O4 also shows good repeatability and reversible responses to CO2 gas. According to the XRD, in situ Raman, and XPS characterization results, the ZnMn2 O4 nanotubes react with CO2 molecules based on a disproportionation reaction mechanism, since the MnCO3 and ZnMnO3 are generated and can be identified during the detection process. Our results indicate that the ZnMn2 O4 nanotubes show great application potentials for CO2 sensing in both air and inert atmospheres.